Procurement Strategy for Organic Coconut Sugar: Case Study of XYZ Company - Eva Saputri Murwaningrum; Erlinda Nusron Yunus (School of Business, IPB University (SB-IPB), 2024)
This study aimed to develop an effective procurement strategy to ensure the supply of PT XYZ's organic coconut sugar in 2023-2025. PT XYZ was a manufacturing company that focused on providing added value to natural commodities produced by farmers in Indonesia. The demand for organic coconut sugar increased every year. However, there were obstacles in procuring organic coconut sugar in terms of farmers' supply capabilities and suitability of specifications. To determine the procurement strategy for organic coconut sugar that could be developed by PT XYZ, an analysis of the sourcing strategy was carried out using the Kraljic Portfolio Matrix method. Organic coconut sugar material was in the strategic material quadrant with high supply risk and high-profit impact. The partnership strategy was the best choice for PT XYZ in 2023-2025, which solved company problems and could also be a productivity improvement solution for companies in Indonesia. Keywords: coconut sugar organic, kraljic portfolio matrix, procurement strategy, coconut sugar productivity, supply risk